Low gamma shift blue-phase liquid crystal display with electric field induced multi-domain electrode structure. Issue 1 (2nd January 2020) - Guo, Yuqiang; Li, Xiaoshuai; Sun, Yan; Zhang, Chi; Yang, Yanling; Zhang, Hui; Ma, Hongmei; Sun, Yubao
ABSTRACT: To reduce the gamma shift of blue-phase liquid crystal display (BPLCD), the multi-domain electrode structure with four sub-electrodes is proposed. The effects of electrodes' parameters on electro-optical curve and gamma shift are calculated, and the gamma shift and contrast ratio at full viewing-cone are also investigated. For the proposed protrusion BPLCD, the operating voltage is reduced by 73%, and the transmittance is increased by 20% compared with the conventional in-plane switching BPLCD. The results also show that the off-axis image distortion index can be reduced from 0.4318 to 0.0875 at the polar angle of 60°, and it works well under various electrodes' sizes. Moreover, the indistinguishable gamma shift can be obtained at full viewing-cone for the proposed BPLCD, and the uniform light distribution and high contrast ratio can be obtained as well. GRAPHICAL ABSTRACT: